Texto publicitário e Letramento Crítico no Livro Didático de língua portuguesa: ampliando paradigmas de leitura - Oliveira, Rogério Macedo de (Universidade Federal de São Carlos, 2018)
The following master thesis intends to investigate reading activities related to advertising texts by conducting comparative analysis between two High School Portuguese textbooks (Brazil, PNLD-2015) whose sessions present reading and comprehension activities directly related to the mentioned discursive genre. By taking into consideration the wide presence of advertising texts in many social contexts, as well as their goals to persuade target audiences by mobilizing strategies to promote a product, idea or concept, language gains a central role and highlights the importance of encouraging students to develop critical and reflective postures on the advertisement increase seen nowadays. Based on such a context, this work aims to conduct a detailed, comparative analysis of reading and comprehension activities presented in these two Portuguese textbooks by exploring theoretical studies related to Critical Literacy and reading activities (LUKE; FREEBODY, 1997; JORDÃO, 2013, 2017; KLEIMAN, 2005; MENEZES DE SOUZA, 2011). Theoretical studies related to advertising knowledge area (SANTOS, 2005) and to the role of multimodalities to create different meanings (KRESS,2003, 2010) were also taken into consideration, as well as the study of Brazilian official documents that regulate the production of textbooks distributed to public schools (BRAZIL, 2013, 2014). Based on the previous considerations, the main objective of this work was to investigate how or in which ways reading and comprehension activities related to advertising texts presented in the selected textbooks (Português: contexto interlocução e sentido and Ser Protagonista: Língua Portuguesa) could favor or even inhibit the promotion of Critical Literacy. In addition, suggestions to amplify or even reconfigure some of the activities were also done to elucidate how the exercises could be articulated to Critical Literacy theories. Results obtained from such research helped to develop considerations related to the theoretical and methodological principles held by both the analyzed reading activities and the Teacher’s guide presented in the textbooks, since most of them were not close to a Critical Literacy reading approach when compared to reading principles sustained by some official documents.
Advertising texts and Critical Literacy in Portuguese textbooks: expanding reading paradigms
Keywords: Texto publicitário; Leitura; Letramento Crítico; Livro didático; Advertising texts; Reading; Critical Literacy; Textbook; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA